Knowledge, Attitudes and Practices towards prevention of Dental Caries among youths aged 15-25 years in Soroti Regional Referral Hospital, Soroti District. A Cross-section Study. - Obuku , Stanley; Kalungi, Vincent Charles (Student's Journal of Health Research Africa, 2022)
Background: The purpose of the study was to assess; the knowledge, attitude, and practices toward the prevention of dental caries among youths aged 15-25 years in Soroti Regional Referral Hospital, Soroti district. The specific objectives of the study were to assess; the knowledge towards prevention of dental caries among youths aged15-25 years, attitudes towards prevention of dental caries among youths aged 15-25 years, and practices towards prevention of dental caries among youths aged 15-25 years. Methodology: A cross-section study design was employed with sampling technique as a sampling technique. Data was collected from a sample of 50 respondents using a semi-structured questionnaire written in the English language; later analyzed manually; using a scientific calculator, and systematically computed into frequency and percentages using Microsoft excel to generate tables and figures for easy presentations. Results: About practices towards prevention of dental caries among youths aged 15-25 years; results showed that (70%) of the respondents were using fluoridated toothpaste, (90%) commonly used toothpaste and toothbrush, (60%) used to take sugar-containing snacks, and (40%) were eating them daily, (60%) reported a brush and paste as oral cleaning habit that they normally used and (80%) reported cleaning their teeth once daily. Conclusion: The researcher generally concluded that; even though study participants exhibited fair knowledge about the prevention of dental caries but their attitude and practices were not worthy agreeable since almost all respondents had an average attitude towards the prevention of dental caries and also doing some practices that are not in line with the prevention of dental caries. Recommendation; the government together with the ministry of health should improve on the sensitization of people about oral health and put up restrictions that can reduce the accessibility of sugar-containing products like snacks hence preventing dental caries among youths of Soroti district.